Vloga šivalnega stroja v socialni in gospodarski zgodovini vsakdanjega življenja v 19. in prvi polovici 20. stoletja - Hönig, Nataša (Prispevki za novejšo zgodovino, 2024)
The article focuses on the sewing machine’s role in economic and social history. First, it examines the long development and the marketing and advertising techniques that enabled the sewing machine to find a place in people’s everyday lives. The second part of the article explores the Slovenian territory, the development of the education system, and, consequently, the development of the seamstress profession.
Keywords: Austria-Hungary; Avstro-Ogrska; dressmaking craft; education; gospodinjstvo; housekeeping; izobraževanje; Kingdom of SCS; Kraljevina SHS/Jugoslavija; oblačilna obrt; podjetje Singer; seamstress; sewing machines; Singer Company; šivalni stroji; šivilje; Yugoslavia